Facilitating Student Voice through Sandwich Principle of Teaching (SPoT): Research-Led Teaching in English Language Teaching (ELT) (NOBEL: Journal of Literature and Language Teaching, 2022)
This study explores the implementation of the Sandwich Principle of Teaching (SPoT) in facilitating the students to voice their thoughts properly while learning about research in English Language Teaching (ELT). This case study is guided by the theory of research-led teaching from Walkington and SPoT from Wahl. The study employed 30 students of higher education as research participants. In 14 weeks, the teacher alternately used traditional and collaborative learning. The students were involved in various learning experiences; formulating lesson goals, reading journal articles, selecting the article, identifying the gap, and choosing and defining research topics. The findings revealed that the integration of SPoT into research-led teaching provides guidance for the teacher to teach research and space to voice their thought under the language learning research program. The findings show a positive attitude on students’ experiences in each stage of the learning research program through SPoT. Based on the findings, it is concluded that the integration of SPoT into research-led teaching could provide the students a space to voice their thought in the language learning research program. They got better learning experiences as they could engage actively in the class and voice their thoughts as well.